2003
DOI: 10.2135/cropsci2003.1358
|View full text |Cite
|
Sign up to set email alerts
|

Yield Adjustment by Canola Grown at Different Plant Populations under Semiarid Conditions

Abstract: populations (Ͻ22 plants ha Ϫ1 ) with the highest population during the season (144 to 200 plants ha Ϫ1 ). Canola Establishing a good canola (rapeseed; Brassica napus L.) stand is yield plasticity in that study varied widely indicating the difficult in the semiarid prairie region of Canada where low temperature, water stress, and soil crusting could result in poor seed bed importance of weather conditions in determination of conditions. A field study was conducted from 1999 to 2001 at Swift the optimum populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
158
5
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(186 citation statements)
references
References 18 publications
15
158
5
8
Order By: Relevance
“…Pea populations were consistently above the minimum of 30 plants m (2 required to obtain maximum pea yields in southwestern Saskatchewan (Johnston et al 2002b). Similarly, canola populations were above the threshold of 40 plants m (2 required for good yield potential at Swift Current (Angadi et al 2003). In a few cases, the wheat population was lower than our target of 80Á100 plants m (2 .…”
Section: Plant Densitymentioning
confidence: 62%
“…Pea populations were consistently above the minimum of 30 plants m (2 required to obtain maximum pea yields in southwestern Saskatchewan (Johnston et al 2002b). Similarly, canola populations were above the threshold of 40 plants m (2 required for good yield potential at Swift Current (Angadi et al 2003). In a few cases, the wheat population was lower than our target of 80Á100 plants m (2 .…”
Section: Plant Densitymentioning
confidence: 62%
“…Moreover, the findings of Gan et al (2004) are based on total seed yield and should be interpreted carefully. If compensation mechanisms are active (Figure 4; Angadi et al, 2003), total seed yield might not be the best measure to determine a developmental sensitivity window.…”
Section: Identification Of a Developmental Sensitivity Windowmentioning
confidence: 99%
“…Studies that quantify the heat stress response by total seed or fruit yield will have less power to identify effects that are only present in a small developmental window. Compensation mechanisms of plants (Figure 4; Angadi et al, 2003;Young et al, 2004) make total seed or fruit yield as a measure even less reliable. Our findings should increase awareness of the fact that the regulation of a trait of interest can change during development.…”
Section: Gwa Mapping Reveals Stage-specific Qtlsmentioning
confidence: 99%
“…Decrease in the number of pods under stress conditions may result from plant inability to create lateral branches because of salt stress intensity and its weakness, which could finally result in decreasing number and size of formed pods. The yield of canola depends on density, number of pods per plant, number of seeds per pod and mass of the seeds (Angadi et al, 2003). Diepenbrock (2000) reported that in rapeseed the number of pods on plant is the most important part of its yield component.…”
Section: And Discussionmentioning
confidence: 99%